THE MOTHER’S ROLE AGAINTS BEHAVIOR OF SURFERER DOWN SYNDROME IN WASHING HAND (Studied in the village of Karangpatihan district of Balong Ponorogo regency) - Putri Meliana Sugianto; Zainul Arifin; . Suhardono (STIKES Insan Cendekia Medika Jombang, 2015)
Down syndrome is a genetic material condition which causes delay of child’s genetic.Theparentsoftenisolatetheir childrenwhosuffer fromdevelopmentaldisorders (down syndrome) duetochromosomal abnormalitiesorbearerof human nature. Therefore, childrenwith the syndromeis consideredtobe afamilydisgracespreader. Mothersoftenignoreself-carefor children with down syndrome especially interms ofhand washing. The research aimed toknowthe influencebetween mother’s role againts behavior ofsurferer down syndrome in the village of Karangpatihan district of Balong Ponorogo regency.The design in this research was analitical with cross sectional approach. The sampel were 33 of 89populations. Using simple random sampling technique. Data collected by using a questionnaire andobservation then data processed with Chie Square test to see the effect of mother’s role againts behavior ofsurferer down syndrome in washing hand. Data was presented in frequency distribution and Crosstabs .This research result obtained that the mother who played active role as many as 17 people (51,5%), andinactive was 16 people (48,5%). While on the behavior of surferer down syndrome obtained results that thesurferer who did good washing hand rightly as many as 20 people ( 60,6%) and who did wrong was as manyas 13 people (39,4%) and the result of statistic test obtained 0,008 that means so H1 accepted and H0rejected this means there’s effect between mother’s role againts behavior of surferer down syndrome inwashing hand in he village of Karangpatihan district of Balong Ponorogo regency.The conclusion in this research was there’s an effect of mother’s role againts behavior of surferer downsyndrome in washing hand in the village of Karangpatihan district of balong, Ponorogo regency.Keywords : Mother’s role, behavior, Down syndrome